2020
DOI: 10.1080/14735903.2020.1721237
|View full text |Cite
|
Sign up to set email alerts
|

Generational dynamics of agricultural intensification in Malawi: challenges for the youth and elderly smallholder farmers

Abstract: In the next 24 years, the Malawian population is expected to double, a development that will inevitably affect access to land and land holding sizes. As access to land is already limited, securing food for the growing population will require policy shifts including the promotion of agricultural intensification. Malawi's economy depends on the agricultural sector, and this paper addresses the generational perspective of agricultural intensification, with specific focus on youth and elderly in smallholder produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 23 publications
1
19
0
1
Order By: Relevance
“…For youth, these challenges include poor and/or limited infrastructure [1,14], and a lack of access to finance, production inputs and resources, markets, extension services, and training [15,16]. Additionally, youths are seen competing with older and more established farmers for resources [17]. The youth's socioeconomic environment mainly portrays farming as a "poor man's" occupation, characterised by long working hours with low economic returns and social status [18].…”
Section: Introductionmentioning
confidence: 99%
“…For youth, these challenges include poor and/or limited infrastructure [1,14], and a lack of access to finance, production inputs and resources, markets, extension services, and training [15,16]. Additionally, youths are seen competing with older and more established farmers for resources [17]. The youth's socioeconomic environment mainly portrays farming as a "poor man's" occupation, characterised by long working hours with low economic returns and social status [18].…”
Section: Introductionmentioning
confidence: 99%
“…The findings show that agriculture attracts a significant number of youths compared to men and women combined, asserting that it is the main source of livelihood for rural youths in the country. Many Malawians depend on agriculture because it plays an overwhelmingly important role in Malawi's economy, accounting for about 30% of the country's GDP (Ng'ong'ola, 2020; Lindsjö et al, 2021). The results further indicate that most household heads are men (96%), thus affirming cultural narratives where men are considered the rightful heads of their families (Bassey and Bubu, 2019).…”
Section: Descriptive Resultsmentioning
confidence: 89%
“…from SAI, and the perceptions of women, youth and elderly regarding the restrictions and enablers of their participation in the transition towards agricultural intensification (Fischer et al, 2020;Lindjö et al, 2020;Zulu et al, 2020). Lindjö et al (2020) observed that young and productive farmers were often lacking access to land, whereas elderly farmers withholding this land were increasingly unable to use this resource productively. Here, the age-determined inequity in access to resources implies a clear break on agricultural intensification.…”
Section: Enabling Smallholders To Benefit From Saimentioning
confidence: 99%